Using the law to change the custom - Gani Aldashev; Imane Chaara; Jean-Philippe Platteau; Zaki Wahhaj (Fondazione Eni Enrico Mattei (FEEM), 2010)
We build a simple model of legal dualism in which a pro-poor legal reform, under certain conditions, causes the conflicting custom to go some way toward producing the change intended by the legislator. It then acts as an 'outside anchor' that exerts a 'magnet effect' on the custom. We illustrate this insight using examples on inheritance, marriage, and divorce issues in Sub-Saharan Africa and India. We also characterize the conditions under which a moderate pro-poor reform is more effective than a radical reform.
Keywords: K40; O17; D74; 330; Custom; Statutory Law; Inequality; Legal Reform